The disciplining effect of supervisory scrutiny in the EU-wide stress test - Christoffer Kok Sørensen; Carola Müller; Steven Ongena; Cosimo Pancaro (European Central Bank (ECB), 2021)
Using a difference-in-differences approach and relying on conftdential supervisory data and an unique proprietary data set available at the European Central Bank related to the 2016 EU-wide stress test, this paper presents novel empirical evidence that supervisory scrutiny associated to stress testing has a disciplining effect on bank risk. We ftnd that banks that participated in the 2016 EU-wide stress test subsequently reduced their credit risk relative to banks that were not part of this exercise. Relying on new metrics for supervisory scrutiny that measure the quantity, potential impact, and duration of interactions between banks and supervisors during the stress test, we find that the disciplining effect is stronger for banks subject to more intrusive supervisory scrutiny during the exercise.
Keywords: G11; G21; G28; 330; Stress Testing; Credit Risk; Internal Models; Banking Supervision; Banking Regulation